Análisis al sistema de salud del Choco y sus efectos para afrontar la contingencia covid - 19 - Arias Arias, Cadry Licek (Universidad Antonio Nariño, 2021)
The provision of health service in the department of Choco is very bad, it seems that for the local government, the inhabitants of this territory do not have the right to satisfy this need, which is a priority for living. They do not have the necessary means to provide this service with quality. Corruption is the greatest impediment to the development of this sector, it has wreaked havoc with health resources, reasons why not, it has a third-level hospital, the only second-level hospital there is, is the San Francisco Hospital Assisi; has been intervened on several occasions, does not have the adequate conditions and tools necessary to face a pandemic such as the covid 19.